(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2017)
This study is about the development of the first competition of nautical sports in Rio Grande do Sul, Brasil, in the early XIX century. To the documental corpus were used the mainly newspapers from that period, in the cities: Rio Grande, Porto Alegre and Pelotas. These newspapers were analyzed with the qualitative data analysis software: ATLAS.ti 7.5.6. The first manifestations of nautical competitions took place in the port cities Rio Grande, Porto Alegre and Pelotas. With the advent of clubs, were adopted the first sporting boats from abroad especially for the races. Such statements show that the clubs had a leading role for the establishment of nautical practices in the Rio Grande do Sul scenario. Furthermore, the competitions were translated to Rio Grande do Sul reality from regattas European model.